Australian hydroclimate during Marine Isotope Stage 3: A synthesis and review. (15th January 2019) - Kemp, C.W.; Tibby, J.; Arnold, L.J.; Barr, C.
Abstract: Improved reconstructions of Australia's climate during Marine Isotope Stage 3 (MIS 3) are important for understanding the environmental context of widespread human settlement of the continent and the extinction of a wide range of megafauna by 45 ± 5 thousand years ago (ka). To better understand spatial and temporal climate trends during this period, we present a synthesis of hydroclimate data from 40 Australian MIS 3 records. Hydroclimate records were evaluated and weighted by a scoring system developed to evaluate dating and proxy quality and resolution before inclusion into the synthesis. Our analysis reveals that Australia experienced spatially variable climates from ∼57 to 49 ka before becoming predominantly wet from ∼49 to 40 ka. After ∼40 ka increasingly dry climates dominated MIS 3. Records from monsoon-influenced regions indicate a rapid drying from ∼48 ka to the end of MIS 3, while there was a wetter period from ∼50 to 40 ka in south westerly wind-influenced records. The implications of our findings are discussed in relation to other proxy records, with there being a significant relationship with regional fire history, but little correlation to atmospheric CO2 concentration or global sea level. Highlights: A synthesis method for forty MIS 3 Australian hydroclimate records is detailed. Greater-than-modern mean water availability peaks at ∼49 to 40 ka before drying. Rapid drying observed in monsoonal records from ∼48 ka. Wetter period observed in south westerly wind-dominated sites ∼50 to 40 ka. The synthesised hydroclimate is significantly correlated to the Australasian charcoal record.